Indonesia's Energy Security Strategy through the Just Energy Transition Partnership: Implications for Energy Sovereignty - Faiz Mumtaz; Dadan Suryadipura (Universitas Jenderal Ahmad Yani, 2026)
Global energy instability has encouraged countries to position energy as a strategic commodity. This article examines how the Just Energy Transition Partnership (JETP) influenced Indonesia’s energy security and its implications for energy sovereignty during 2022-2024. Drawing on Cherp and Jewell’s (2011) sovereignty perspective, the study employs qualitative research of primary and secondary data through three dimensions: control over the energy system, diversification and reduction of external vulnerabilities, and autonomy in energy transition governance. The findings show that JETP partially strengthens Indonesia’s energy sovereignty by diversifying the power sector, expanding transition capacity, and preserving national policy leadership. However, by 2024, Indonesia’s energy system remained dependent on fossil and imported fuels, while the transition was increasingly tied to foreign financing and technology. The article argues that JETP doesn’t eliminate vulnerability but shifts dependence towards external capital and technological networks. Thus, the JETP’s role in strengthening Indonesia’s energy security remains partial.